Prenatal diagnosis of Simpson–Golabi–Behmel syndrome. Issue 12 (9th September 2016) - Magini, Pamela; Palombo, Flavia; Boito, Simona; Lanzoni, Giulia; Mongelli, Patrizia; Rizzuti, Tommaso; Baccarin, Marco; Pippucci, Tommaso; Seri, Marco; Lalatta, Faustina
Abstract : Simpson–Golabi–Behmel syndrome (SGBS) is an overgrowth syndrome and it is usually diagnosed postnatally, on the basis of phenotype. Prenatal ultrasonography may show fetal alterations, but they are not pathognomonic and most of them are frequently detectable only from the 20th week of gestation. Nevertheless, early diagnosis is important to avoid neonatal complications and make timely and informed decisions about the pregnancy. We report on four fetuses from two unrelated families, in whom the application of whole exome sequencing and array‐CGH allowed the identification of GPC3 alterations causing SGBS. The careful follow up of pregnancies and more sophisticated analysis of ultrasound findings led to the identification of early prenatal alterations, which will improve the antenatal diagnosis of SGBS. © 2016 Wiley Periodicals, Inc.